2018
DOI: 10.1111/mec.14872
|View full text |Cite
|
Sign up to set email alerts
|

Assessing changes in arthropod predator–prey interactions through DNA‐based gut content analysis—variable environment, stable diet

Abstract: Analysing the structure and dynamics of biotic interaction networks and the processes shaping them is currently one of the key fields in ecology. In this paper, we develop a novel approach to gut content analysis, thereby deriving a new perspective on community interactions and their responses to environment. For this, we use an elevational gradient in the High Arctic, asking how the environment and species traits interact in shaping predator-prey interactions involving the wolf spider Pardosa glacialis. To ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 93 publications
2
76
1
Order By: Relevance
“…Nevertheless, significant interspecific and inter‐clade differences in isotopic signature persist when datasets are controlled for year and elevation (Figures S1 and S2). Interestingly, another recent study found that spiders' diets do not change over elevational gradients despite differences in the prey community over these gradients (Eitzinger et al, ), though isotopic differences due to climatic variation may still occur between different elevations.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, significant interspecific and inter‐clade differences in isotopic signature persist when datasets are controlled for year and elevation (Figures S1 and S2). Interestingly, another recent study found that spiders' diets do not change over elevational gradients despite differences in the prey community over these gradients (Eitzinger et al, ), though isotopic differences due to climatic variation may still occur between different elevations.…”
Section: Discussionmentioning
confidence: 99%
“…We used a single primer pair (SFF‐145f: 5′‐GTHACHGCYCAYGCHTTYGTAATAAT‐3′ and SFF‐351r: 5′‐CTCCWGCRTGDGCWAGRTTTCC‐3′; primers and PCR setup from Walker, Williamson, Sanchez, Sobek, & Chambers, ) to test the DNA extraction success in the pooled samples and confirm the bat species by molecular analysis and another primer pair to amplify the potential prey (ZBJ‐ArtF1c: 5′‐AGATATTGGAACWTTATATTTTATTTTTGG‐3′ and ZBJ‐ArtR2c: 5′‐WACTAATCAATTWCCAAATCCTCC‐3′; primers and PCR setup from Zeale, Butlin, Barker, Lees, & Jones, ). Despite the proposed bias in Zeale primers toward Diptera and Lepidoptera (Clarke, Soubrier, Weyrich, & Cooper, ), we chose these for several reasons: (a) These are the most widely applied markers, (b) many species have been detected using exactly the same primers, even though claimed to be nonamplifiable in the earlier criticism, and (c) we wanted to allow comparison of our results with those of other studies using the same primers (Clare et al, ; Kaunisto, Roslin, Sääksjärvi, & Vesterinen, ; Koskinen et al, ; Krüger, Clare, Greif, et al, ; Krüger, Clare, Symondson, et al, ; Vesterinen et al, ; Wirta et al, ; Eitzinger et al, ). The PCR and library construction closely followed Kaunisto et al (), except we used MyTaq HS Red Mix (product nr BIO‐25048, Bioline, UK) polymerase throughout the protocol.…”
Section: Methodsmentioning
confidence: 99%
“…We focused sampling on roosts inhabited by a single species, and likewise, we intended to pool pellets from a single species into a single pooled sample. In total, we initially sampled 1,252 fecal pellets from the five bat species in this study ( we wanted to allow comparison of our results with those of other studies using the same primers Kaunisto, Roslin, Sääksjärvi, & Vesterinen, 2017;Koskinen et al, 2018;Krüger, Clare, Greif, et al, 2014;Vesterinen et al, 2013Vesterinen et al, , 2016Wirta et al, 2015;Eitzinger et al, 2018). The PCR and library construction closely followed Kaunisto et al (2017), TA B L E 1 Information on the sampling details and characteristics of the field and molecular data.…”
Section: Laboratory Workmentioning
confidence: 99%
“…Molecular dietary analysis-sequencing prey DNA from predator feces or gut contents and identifying them using a reference library (Clare et al, 2009;Eitzinger et al, 2018;Symondson, 2002;Vesterinen et al, 2016;Zaidi, Jaal, Hawkes, Hemingway, & Symondson, 1999)-can be used to reveal the exact food webs in ecosystems. Molecular dietary analysis-sequencing prey DNA from predator feces or gut contents and identifying them using a reference library (Clare et al, 2009;Eitzinger et al, 2018;Symondson, 2002;Vesterinen et al, 2016;Zaidi, Jaal, Hawkes, Hemingway, & Symondson, 1999)-can be used to reveal the exact food webs in ecosystems.…”
mentioning
confidence: 99%